Perception Management, News and Propaganda Relationship in the Cold War Era - ÖZÇAĞLAYAN, MEHMET (MARMARA UNIV, FAC COMMUNICATION, 2017)
The governments that hold the power of being the premium news source of the media can convey their messages to the target group by both propaganda and perception management activities; they can also affect the perception of the target group in accordance with the objective. The study which aimed to evaluate how the news is used as an instrument of propaganda and perception management by The United States in the Cold War era, the headlines of the Washington Post and the New York Times published on the 1953 Iranian Coup and the 1979 Soviet Union's Invasion of Afghanistan are analyzed through Norman Fairclough's critical discourse analysis and it is detected that propaganda was widely used in the news and news content in order to establish an anti-communist perception in the Cold War era.
Keywords: Cold War; Perception Management; Anti-Communism; Propaganda; News